Efficacy and safety of early ultrafiltration in patients with acute decompensated heart failure: a meta-analysis - Chen, Shuai; Wang, Hongqi; Ning, Bin (Frontiers in Cardiovascular Medicine, 2023)
Objective The objective of this study is to investigate the efficacy and safety of early ultrafiltration in patients with acute decompensated heart failure. Methods A systematic search was conducted on PubMed, Cochrane Library, and EMbase databases from inception to April 2023 to identify randomized controlled trials that compared the efficacy and safety of early ultrafiltration and conventional diuretics in patients with acute decompensated heart failure. Two investigators independently screened all eligible studies and extracted relevant data. The primary outcomes of interest were changes in body weight and creatinine levels, as well as the rate of readmission and mortality within 30 days. Meta-analysis was conducted using RevMan 5.4 software. Results This meta-analysis included eight studies and found that early ultrafiltration was effective in reducing body weight in patients with acute decompensated heart failure (RR = 1.45, 95% CI: 0.54–2.35, P = 0.002), but it also increased serum creatinine (RR = 0.1, 95% CI: 0.03–0.17, P = 0.003). However, it did not reduce the 30-day rehospitalization rate or mortality rate (30-day rehospitalization rate: RR = 0.84, 95% CI: 0.62–1.14, P = 0.28; Mortality: RR = 0.90, 95% CI: 0.57–1.44, P = 0.67). Conclusion Although early ultrafiltration is more effective in reducing body weight in patients with acute decompensated heart failure, it is associated with an increase in serum creatinine levels and does not reduce the rate of readmission or mortality within 30 days. Systematic Review Registration identifier: CRD42023416152.